Keramik Situs Gede Ing Suro sebagai Sumber Pembelajaran Sejarah di SMK Muhammadiyah 03 Palembang - Riki Pratama Putera (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
Gede Ing Suro Site Ceramics as a Source of History Learning in SMK Muhammadiyah 3 Palembang. The problem of this research is what historical value is there in the Gede Ing Suro ceramics site which can be used as a source of history learning in class X SMK Muhammadiyah 3 Palembang. The purpose of this study is to determine whether the historical value of the Gede Ing Suro ceramics site can be used as a source of history learning in class X SMK Muhammadiyah 3 Palembang. The method used in this research is descriptive qualitative method. Data collection techniques used were documentation, observation and interviews. The results of the study can be concluded. Ceramics of the Gede Ing Suro site are historic relics which prove that the Gede Ing Suro Site has important historical and cultural values ​​in the past. The historical value of the Gede Ing Suro ceramics site can be used as a source of history learning in class X. By becoming a teaching material Ceramics Site of the Gede Ing Suro as a Historical Learning Resource at SMK Muhammadiyah 3 Palembang, it will help students get to know historical relics, especially local history, namely ceramic site Gede Ing Suro. So that it can motivate maintaining the cultural products in South Sumatra, especially at the Gede Ing Suro Site.